1980
DOI: 10.1051/apido:19800108
|View full text |Cite
|
Sign up to set email alerts
|

BIOCHEMISTRY AND MICROBIOLOGY OF BEE-COLLECTED ALMOND (PRUNUS DULCIS) POLLEN AND BEE BREAD. I- Fatty Acids, Sterols, Vitamins and Minerals

Abstract: SUMMARYAlmond (Prunus dulcis) pollen was hand-and honey bee-collected (corbicular) for chemical analysis. Corbicular pollen was packed by bees into wax combs for conversion (via natural fermentation) into bee bread. Chemical analyses of 12 fatty acids, 3 sterols, 3 vitamins, inositol, titratable acidity, and 5 minerals were made on the hand-collected and corbicular pollen. The bee bread was analyzed after 7, 2l, and 42 days for all of the above except the fatty acids and sterols. Lipoidal and acidic additions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
3
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 23 publications
5
45
3
9
Order By: Relevance
“…Previous studies on the composition and nutritive value of bee bread were done with European honey bees (EHB) (e.g., Loper et al 1980;Human and Nicolson 2006). However, there may be differences in the composition and consumption of bee bread made by bees of different subspecies even when they feed on the same pollen.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the composition and nutritive value of bee bread were done with European honey bees (EHB) (e.g., Loper et al 1980;Human and Nicolson 2006). However, there may be differences in the composition and consumption of bee bread made by bees of different subspecies even when they feed on the same pollen.…”
Section: Introductionmentioning
confidence: 99%
“…They can vary depending on time of collection, climatic conditions, plant age and botanical source. [2][3][4] Basically, it contains vitamins of B complex, vitamin C, D, E and carotenoids, [5][6][7] but there are few data in literature about relationship between botanical origin and vitamin quantification. Muniategui et al 6 observed carotenes in pollen samples from Spain, AlmeidaMuradian et al 8 observed the absence of vitamin C and β-carotene in a processed samples of bee pollen loads from the south of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Para la primera medición (día 0) T 0 y T 5 presentan el mayor promedio de acidez en relación con T 1 y T 2 . Análogamente con lo ocurrido en el caso del pH, se observa que al inicio del ensayo los grupos son relativamente homogéneos; presentando diferencia significativa al transcurrir el tiempo, sin embargo, al final del proceso todos los tratamientos no presentan diferencias estadísticas, pero en general se aprecia un aumento del contenido de acidez titulable, lo que coincide con Loper et al (1980), quienes señalan que la acidez titulable aumenta durante la conversión en pan de abejas. Esto se debe a que, sin importar la cantidad de inóculo, al pasar el tiempo las bacterias irán reproduciéndose y ocupando el sustrato existente (Dustmann, 2007), y al final de la evaluación (día 20) los tratamientos que al inicio tenían menos inóculo, habrán llegado a tener la misma cantidad de bacterias que los otros tratamientos tuvieron al inicio, esto se puede comparar con la elaboración del pan en el proceso de fermentación (García y Navarro, 2007).…”
Section: Acidez Titulableunclassified
“…Sin embargo, Human y Nicolson (2006) reportaron que el contenido de cenizas es significativamente menor en polen almacenado que en polen fresco. Loper et al (1980) exponen que la concentración de minerales en el pan de abejas disminuye a medida que el polen corbicular almacenado en las celdillas se acidifica, esto probablemente refleja la adición de material lipídico por parte de las abejas. Por esta razón se hace necesario conocer las proporciones y características de los elementos que las abejas adicionan a este producto que son propios de su biología, para así obtener la correcta formulación de este producto.…”
Section: Cenizasunclassified
See 1 more Smart Citation